Collins Cobuild English grammar - Collins, Cobuild (HarperCollins, 2005)
This new edition of the Collins COBUILD English Grammar provides teachers and advanced learners with a detailed and thorough analysis of modern English grammar. Based on the evidence of the Bank of English corpus, part of the 2.5 billion-word Collins Word Web, it is an invaluable guide to the language as it is written and spoken today